Implementasi Beragama Maslahat dan Berkebudayaan Maju dalam Kehidupan Keluarga Muhammadiyah Kota Surakarta - Abadi, Lukman Trijaya (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2025)
The application of the concept of religious welfare and advanced culture is an important strategy in facing the challenges of modernity and in line with the vision of the 2025-2045 RPJPN to build a harmonious, inclusive, and sustainable society. The Muhammadiyah family in Surakarta City as part of one of the largest Islamic organizations in Indonesia, plays an important role in realizing these values through education, philanthropy, and cultural preservation. This study aims to analyze the implementation of the concept of religious welfare and advanced culture in the lives of Muhammadiyah families in Surakarta City, and how these values can help families face the challenges of modernity and contribute to national development. The research method used is a qualitative approach with interview and documentation techniques. Data were obtained from Muhammadiyah family members, related literature, and relevant organizational policies. The results of the study show that Muhammadiyah families in Surakarta have succeeded in internalizing religious values through religion-based education, philanthropy through Lazismu, and inclusive health and education services.